2023
DOI: 10.3390/agriculture13020388
|View full text |Cite
|
Sign up to set email alerts
|

New Spectral Index and Machine Learning Models for Detecting Coffee Leaf Miner Infestation Using Sentinel-2 Multispectral Imagery

Abstract: The coffee leaf miner (Leucoptera coffeella) is a key coffee pest in Brazil that can cause severe defoliation and a negative impact on the productivity. Thus, it is essential to identify initial pest infestation for the sake of appropriate time control to avoid further economic damage to the coffee crops. A fast non-destructive method is an important tool that can be used to monitor the occurrence of the coffee leaf miner. The present work aims to identify the occurrence of coffee leaf miner infestation throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…In this study, it was observed that healthy plants had a higher mean reflectance of the EDGE, G, NIR and R bands than infested plants. This result is consistent with the studies conducted by Vilela et al [17] in which the authors observed that the spectral response in the NIR region of a coffee crop with a higher percentage of leaf miner infestation was lower than that of a crop with a lower percentage of infestation. That is, the greater the reflectance, especially in the NIR region, the more this spectral behaviour is related to vegetative vigour.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, it was observed that healthy plants had a higher mean reflectance of the EDGE, G, NIR and R bands than infested plants. This result is consistent with the studies conducted by Vilela et al [17] in which the authors observed that the spectral response in the NIR region of a coffee crop with a higher percentage of leaf miner infestation was lower than that of a crop with a lower percentage of infestation. That is, the greater the reflectance, especially in the NIR region, the more this spectral behaviour is related to vegetative vigour.…”
Section: Discussionsupporting
confidence: 93%
“…These mines cause leaf necrosis, contributing to a lower photosynthetic rate [4] and, therefore, lower vigour and lower spectral response in the NIR range. Thus, the infestations of pests that affect the internal structures of the leaves can be evaluated using the NIR band, confirming the results of this study and some previous studies [17,40] and highlighting the importance of spectral bands in RF classifications, as demonstrated by the Gini index (Figure 5).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The prior studies have demonstrated that incorporating vegetation features into the extraction of crop distribution information from remote sensing imagery can result in improved discrimination between vegetation and non-vegetation, as well as different types of vegetation, compared to relying solely on the original four spectral bands [36][37][38]. This study employed prior knowledge to extract four additional vegetation indices from the original four spectral bands, namely the Normalized Difference Vegetation Index (NDVI), Green Normalized Difference Vegetation Index (GNDVI), Optimal Soil Adjusted Vegetation Index (OSAVI), and Canola Index (CI) [17,39].…”
Section: Vegetation Featurementioning
confidence: 99%
“…The Green-Red Normalized Difference Vegetation Index (GRNDVI) was the most effective factor in differentiating between infected and healthy leaves, with average values of 0.32 for healthy leaves and 0.06 for infected leaves. In another study [7], the authors developed a specific vegetation index to estimate coffee leaf miner infestation using Sentinel-2 multispectral images called the Coffee-Leaf-Miner Index (CLMI). The authors employed machine learning (ML) techniques to recognize infestation patterns in coffee plantations.…”
Section: Introductionmentioning
confidence: 99%